Systolic Blood Pressure Variability and Risk of Ischemic Stroke in Patients Receiving Hemodialysis - Mu-Yang Hsieh; Li-Kai Tsai; Ru-Yin Hsu; Meng-Kan Chen; Chung-Wei Yang; Shao-Yuan Chuang; Ting-Ju Lai; Hao-Ming Cheng; Chih-Cheng Wu (Clinical Journal of the American Society of Nephrology, 2026)
Background and objectives: Blood pressure variability (BPV) has been recognized as a cardiovascular risk factor beyond mean blood pressure, but its role in ischemic stroke among patients receiving hemodialysis remains incompletely defined, particularly across stroke subtypes. We evaluated the association between visit-to-visit BPV and incident ischemic stroke in a multicenter hemodialysis cohort. Design, setting, participants, & measurements: In this prospective cohort study, 1,136 patients undergoing maintenance hemodialysis were enrolled from 12 centers. Pre-dialysis blood pressure measurements were collected over a standardized 12-week baseline period (approximately 36 readings per patient). BPV was quantified using the coefficient of variation (CV) and analyzed per 10% greater CV and by tertiles. The primary outcome was incident ischemic stroke, including large artery atherosclerosis (LAA) and small vessel occlusion (SVO). Fine–Gray competing risk models were used to estimate subdistribution hazard ratios (sHRs), adjusting for demographics, blood pressure, comorbidities, medication, and dialysis-related factors. Results: During a median follow-up of 54 months, 144 patients developed ischemic stroke. Higher systolic BPV was independently associated with greater stroke risk (sHR per 10% greater CV, 1.74; 95% confidence interval [CI], 1.10–2.76, P=0.02) in the clinically adjusted model, with consistent findings in extended analyses. In subtype-specific analyses, systolic BPV was significantly associated with LAA and showed a directionally consistent but attenuated association with SVO after extended adjustment. In contrast, diastolic BPV showed weaker associations that were not statistically significant after multivariable adjustment. Conclusions: Higher systolic BPV was independently associated with ischemic stroke in patients receiving hemodialysis, with the most consistent subtype-specific association observed for large artery atherosclerosis. These findings suggest that systolic BPV may serve as a clinically accessible marker of cerebrovascular risk beyond mean blood pressure in this high-risk population.